2021
DOI: 10.3389/fmed.2021.769335
|View full text |Cite
|
Sign up to set email alerts
|

The Glomerular Filtration Rate: From the Diagnosis of Kidney Function to a Public Health Tool

Abstract: The prevalence of chronic kidney disease (CKD) continues to increase worldwide, as well as the associated morbidity and mortality and the consequences on the patients' quality of life and countries' economies. CKD often evolves without being recognized by patients and physicians, although the diagnosis is based on two simple laboratory data: the estimated glomerular filtration rate (eGFR) and urine analysis. To measure GFR, the knowledge about the physiologic processes at the nephron level, the concept of clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
(51 reference statements)
0
4
0
1
Order By: Relevance
“…There are several examples in medicine in which tests or compounds far removed from the original target become instrumental laboratory tools. For instance, creatinine levels are used as proxy of kidney function, even though creatinine is not part of the renal system [ 181 ]. Another example is the Venereal Disease Research Laboratory (VDRL) in use to diagnose syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…There are several examples in medicine in which tests or compounds far removed from the original target become instrumental laboratory tools. For instance, creatinine levels are used as proxy of kidney function, even though creatinine is not part of the renal system [ 181 ]. Another example is the Venereal Disease Research Laboratory (VDRL) in use to diagnose syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we collected glycated hemoglobin (HbA1c) (%), total cholesterol (TC) (mmol/L), triglycerides (TG) from laboratory examination data. We calculated the estimated glomerular filtration rate (eGFR) based on the creatinine data of participants provided by NHANES using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) method ( 25 ). Hypertension was diagnosed based on guidelines provided by the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure.…”
Section: Methodsmentioning
confidence: 99%
“…This renal clearance of phenylacetylglutamine is inversely related to the plasma levels of PAGln and is stronger among patients with normal renal function than in patients with abnormal renal function . Accumulation of these gut-derived uremic toxins–PAGln is observed among uremic patients. The glomerular filtration rate (GFR) is an accurate estimate of kidney function, and its alteration is observed in the case of kidney diseases . Some investigations have shown a direct correlation between chronic kidney disease (CKD) and cardiovascular disease (CVD) .…”
Section: Excretion Of Phenylacetylglutaminementioning
confidence: 99%
“… 28 30 The glomerular filtration rate (GFR) is an accurate estimate of kidney function, and its alteration is observed in the case of kidney diseases. 31 Some investigations have shown a direct correlation between chronic kidney disease (CKD) and cardiovascular disease (CVD). 32 In a study that correlates urine metabolites to nephropathy, it was reported that glutamine levels were lower in Type-2 DM patients in comparison to controls with albuminuria.…”
Section: Excretion Of Phenylacetylglutaminementioning
confidence: 99%